Two-year prospective study on various anti-epileptic drugs in drug-resistant epilepsy patients and parameters affecting seizure-freedom in Eastern Indian subcontinent - Mukherjee, Joydeep; Guha, Gautam; Saha, Shankar Prasad (Asian Journal of Medical Sciences, 2019)
Background: Epilepsy is a disease of suffering. Drug-resistant epilepsy (DRE) takes a heavy toll on patients, family and society in the form of prolonged treatment, expenditure, unemployment and disability. Successful treatment depends on appropriate antiepileptic drug (AED) use in appropriate dosage, which varies in different parts of the world. Aims and Objectives: To find out AED efficacy in Indian subcontinent and factors affecting seizure freedom. Materials and Methods: We explored many characteristics of DRE patients, compared in between seizure-free and seizure-persisting patients to find out the variables more affecting seizure-freedom. We measured minimum effective dose and maximum tolerable dose of different AED in child and adult subgroups in patients of the Indian subcontinent. Results: Lamotrigine was most efficacious in various seizure-types and phenytoin was the least one as first add-on AED. Clobazam was efficacious and good-compliance second add-on AED. AED compliance was significantly reduced as the number of AED was increased above two. AED monotherapy was most effective and the effectiveness decreased as subsequent AED was added as per need. Conclusion: Our study enlightened about various aspects of drug-resistant epilepsy patients in Indian sub-continent and their treatment.